Ultrasound-guided percutaneous microwave ablation of primary hyperthyroidism: security and efficacy analysis - Jing-E Zhu; Chun-Jun Sheng; Hui-Li Zhang; Jia-Xin Li; Xiao-Wan Bo; Jia-Jing Yin; Peng Yang; Song-Yuan Yu; Li-Ping Sun (International Journal of Hyperthermia)
Objectives This study aimed to analyze the safety, efficacy, and application prospects of ultrasound-guided microwave ablation (MWA) in the treatment of primary hyperthyroidism.Methods Eight patients with primary hyperthyroidism who underwent ultrasound-guided glandular volume reduction between January 2021 and December 2022 were included in this study. Pre- and postablative examinations, including grayscale ultrasound, contrast-enhanced ultrasound (CEUS), laboratory examination, antithyroid drug (ATD) dosage, and quality of life (QoL) assessment via Thyroid-Specific Patient-Reported Outcome Short-Form (ThyPRO-39), were analyzed retrospectively. The main ultrasound follow-up times were 1, 3, 6, and 12 months after ablation. Thyroid function was reviewed 1 week after ablation, and the subsequent reexamination time was determined according to the patient’s specific test results and ATD adjustment. The final efficacy was comprehensively analyzed according to the patient’s medication status, thyroid function, thyroid volume, and QoL score.Results All 8 patients successfully received MWA for primary hyperthyroidism, and none of them experienced serious complications. By the end of the follow-up, 5 of the 8 patients had stopped taking ATDs, 3 of the 8 patients had reduced ATD dosages, and all of them maintained stable thyroid function. Although descriptive analysis was performed because of the small sample size, patients’ thyroid volume reduction, and obvious improvements in goiter symptoms, hyperthyroid symptoms, anxiety, etc., were observed during our follow-up.Conclusion Ultrasound-guided MWA for reducing thyroid gland volume in primary hyperthyroidism patients is a new, safe, and effective minimally invasive treatment method that is a good choice for patients who cannot or refuse traditional treatment methods.